Effect of Hot Deformation Temperature on Texture Formation Regularity of CGO Silicon Steel under High Deformation Rate - Zhi-chao Li; Ning Dang; Zhen-li Mi (Advances in Materials Science and Engineering)
The influence of hot deformation temperature on microstructure and texture of CGO silicon steel under the condition of a high deformation rate (100 s-1) was studied by SEM and EBSD techniques. The results indicate that the typical microstructures at room temperature consist of ferrite and pearlite under different hot deformation temperatures. The higher deformation temperature is beneficial to obtain a more uniform recrystallization microstructure and lower pearlite content. Cubic texture {100}001 and rotated cubic texture {100}011 are dominant texture components in the tested steels, and {111}112 texture in γ fiber is also strong, the intensity of which is higher than that of {111}110 texture. Goss texture {110}001 is weak. With the rising of the hot deformation temperature, {100}011 texture decreases firstly and then increases at 1100°C. When the hot deformation temperature raises from 800°C to 900°C, {111}112 texture shows an increasing trend, while {111}110 texture content is stable. When the temperature further increases to 1100°C and 1150°C, {111}112 and {111}110 textures are slightly weakened.